Familial juvenile onset Alexander Disease demonstrating germline mosaicism and presenting with a tumor-like mass of the medulla. (May 2021) - Dunham, C; Sargent, M; Halverson, M; Hukin, J; Tamber, M; Richardson, A
Abstract : Alexander Disease (AD) is a rare and ultimately lethal leukodystrophy, typically presenting in infants who exhibit developmental delay, macrocephaly, seizures, spasticity and quadriparesis. Classic infantile forms are generally due to sporadic mutations in GFAP that result in the massive deposition of intra-astrocytic Rosenthal fibres, particularly in the frontal white matter. However, phenotypic manifestations are broad and include both juvenile and adult forms that often display infratentorial pathology and a paucity of leukodystrophic features. We describe the unique case of an 8.5 year old female who presented with an 8 month history of progressively worsening vomiting and cachexia, whose extensive multidisciplinary systemic workup, including GI biopsies, proved negative. Neuroimaging ultimately revealed bilaterally symmetric and anterior predominant supratentorial signal alterations in the white matter plus a 1.7 x 1.2 x 0.7 mm right dorsal medullary mass. Biopsy of this presumed low-grade glioma revealed features in keeping with AD, which was later confirmed on whole exome sequencing. The proband exhibited a pathogenic p.Arg239Cys heterozygous missense mutation in GFAP, which was apparently inherited from her asymptomatic mother (1% mosaicism in the mother's blood). Germline mosaic inheritance patterns of young-onset AD, particularly those presenting with a tumor-like mass of the brainstem, are scarcely reported in the literature and serve to expand the clinicopathologic spectrum of AD. LEARNING OBJECTIVES: This presentation with enable the learner to: 1. Recognize an uncommon clinical presentation of AD. 2. Describe the underlying genetics of AD, including a rare familial juvenile onset form featuring germline mosaicism.